Evaluasi Konstruktivisme Sosial Sebagai Pendekatan Pendidikan Karakter di Era Digital - Hafizi, M Zainul (Jurnal Ilmiah Edukatif, 2023)
This study aims to evaluate the effectiveness of social constructivism approach in shaping student character in the digital era. In the context of the development of information and communication technology, the challenges faced in character education are increasingly complex. Therefore, this study uses the literature review method to analyze related theories, evaluate the impact of the digital era on character formation, and develop a social constructivism model that is suitable for character education in the digital era. The results showed that social constructivism, which emphasizes the role of social interaction, collaboration, and shared learning, has great potential in shaping students' positive character. The social constructivism approach model developed in this study integrates technology as an aid in character learning. Teaching strategies that focus on collaboration, social interaction, and project-based learning encourage students to develop social skills, empathy, and emotional intelligence. Evaluation of the implementation of this model shows improvement in the development of student character. They are able to collaborate better, have a deeper understanding of character values, and can live social interactions positively in the challenging digital age. Recommendations include teacher training in integrating technology in character education, development of appropriate digital learning resources, and parental involvement in supporting character education at home. Support from schools and relevant stakeholders is also considered important in creating an educational environment that supports student character development in the digital era. This research provides an in-depth look at the role of social constructivism and technology in shaping student character in the ever-evolving digital age.